2018
DOI: 10.1080/09537104.2018.1430357
|View full text |Cite
|
Sign up to set email alerts
|

Platelets in wound healing and regenerative medicine

Abstract: Although platelets are widely recognized as having a critical role in primary hemostasis and thrombosis, increasing experimental and clinical evidence identifies these enucleated cells as relevant modulators of other physiopathological processes including inflammation and tissue regeneration. These phenomena are mediated through the release of growth factors, cytokines, and extracellular matrix modulators that sequentially promote (i) revascularization of damaged tissue through the induction of migration, prol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
191
0
6

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 247 publications
(218 citation statements)
references
References 134 publications
0
191
0
6
Order By: Relevance
“…Platelets are recognized in a critical role of primary hemostasis and thrombosis. Recent evidence have shown that platelets also act as a modulators in the process of tissue inflammation and regeneration . PRP injections have been widely applied in treatment of knee osteoarthritis through the anti‐inflammatory effect of platelet related growth factors .…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Platelets are recognized in a critical role of primary hemostasis and thrombosis. Recent evidence have shown that platelets also act as a modulators in the process of tissue inflammation and regeneration . PRP injections have been widely applied in treatment of knee osteoarthritis through the anti‐inflammatory effect of platelet related growth factors .…”
Section: Discussionmentioning
confidence: 99%
“…Recent evidence have shown that platelets also act as a modulators in the process of tissue inflammation and regeneration. 12 PRP injections have been widely applied in treatment of knee osteoarthritis through the anti-inflammatory effect of platelet related growth factors. 19 In addition, PRP has been demonstrated to promote proliferation and migration of skeletal muscle cells in vitro.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations